Directional Janus Metasurface. Issue 2 (20th November 2019) - Chen, Ke; Ding, Guowen; Hu, Guangwei; Jin, Zhongwei; Zhao, Junming; Feng, Yijun; Jiang, Tian; Alù, Andrea; Qiu, Cheng‐Wei
Abstract: Janus monolayers, a class of two‐faced 2D materials, have received significant attention in electronics, due to their unusual conduction properties stemming from their inherent out‐of‐plane asymmetry. Their photonic counterparts recently allowed for the control of hydrogenation/dehydrogenation processes, yielding drastically different responses for opposite light excitation spins. A passive Janus metasurface composed of cascaded subwavelength anisotropic impedance sheets is demonstrated. By introducing a rotational twist in their geometry, asymmetric transmission with the desired phase function is realized. Their broken out‐of‐plane symmetry realizes different functions for opposite propagation directions, enabling direction‐dependent versatile functionalities. A series of passive Janus metasurfaces that enable functionalities including one‐way anomalous refraction, one‐way focusing, asymmetric focusing, and direction‐controlled holograms are experimentally demonstrated. Abstract : Direction‐encoded wave manipulations are experimentally achieved through the use of Janus metasurfaces composed of cascaded metasheets. By introducing a rotational twist in metasurface geometry, asymmetric electromagnetic wavefront manipulation can be realized. This is demonstrated both theoretically and experimentally by a series of passive metadevices, which enable functionalities including one‐way anomalous refraction, one‐way focusing, asymmetric focusing, and direction‐controlled holograms.